Scaling up rehabilitation - Towards an international policy agenda - Christoph Gutenbrunner; Jerome Bickenbach; Kristian Borg; Boya Nugraha; John Melvin; Gerold Stucki (Medical Journals Sweden, 2018)
No Abstract (Guest Editorial)